Defaunation precipitates the extinction of evolutionarily distinct interactions in the Anthropocene - Emer, Carine [UNESP]; Galetti, Mauro [UNESP]; Pizo, Marco A. [UNESP]; Jordano, Pedro; Verdu, Miguel (Amer Assoc Advancement Science, 2019)
Species on Earth are interconnected with each other through ecological interactions. Defaunation can erode those connections, yet we lack evolutionary predictions about the consequences of losing interactions in human-modified ecosystems. We quantified the fate of the evolutionary history of avian-seed dispersal interactions across tropical forest fragments by combining the evolutionary distinctness of the pairwise-partner species, a proxy to their unique functional features. Both large-seeded plant and large-bodied bird species showed the highest evolutionary distinctness. We estimate a loss of 3.5 to 4.7 x 10(4) million years of cumulative evolutionary history of interactions due to defaunation. Bird-driven local extinctions mainly erode the most evolutionarily distinct interactions. However, the persistence of less evolutionarily distinct bird species in defaunated areas exerts a phylogenetic rescue effect through seed dispersal of evolutionarily distinct plant species.